2013
DOI: 10.1016/j.ccr.2013.04.019
|View full text |Cite|
|
Sign up to set email alerts
|

A Critical Role for Notch Signaling in the Formation of Cholangiocellular Carcinomas

Abstract: The incidence of cholangiocellular carcinoma (CCC) is increasing worldwide. Using a transgenic mouse model, we found that expression of the intracellular domain of Notch 1 (NICD) in mouse livers results in the formation of intrahepatic CCCs. These tumors display features of bipotential hepatic progenitor cells, indicating that intrahepatic CCC can originate from this cell type. We show that human and mouse CCCs are characterized by high expression of the cyclin E protein and identified the cyclin E gene as a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
149
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(166 citation statements)
references
References 37 publications
(44 reference statements)
11
149
1
3
Order By: Relevance
“…Our findings, alternatively, suggest that hepatocytes are the source of this ductular outgrowth. Combined with recent findings (Fan et al, 2012; Sekiya and Suzuki, 2012; Zender et al, 2013), our work argues in favor of a new paradigm in which hepatocytes might be the cell-of-origin not only for cholangiocarcinoma but also for mixed-phenotype liver cancer, typically thought to arise from oval cells.…”
Section: Discussionsupporting
confidence: 71%
“…Our findings, alternatively, suggest that hepatocytes are the source of this ductular outgrowth. Combined with recent findings (Fan et al, 2012; Sekiya and Suzuki, 2012; Zender et al, 2013), our work argues in favor of a new paradigm in which hepatocytes might be the cell-of-origin not only for cholangiocarcinoma but also for mixed-phenotype liver cancer, typically thought to arise from oval cells.…”
Section: Discussionsupporting
confidence: 71%
“…41 Aberrant notch signalling is also implicated in liver cancer. 42,43 Notch signalling is vital to normal liver development, and has a major role in biliary lineage determination. 44 Comparative functional genomics identified activation of Notch in around 30% of human HCCs, providing the rationale for selective Notch blockade in a subset of patients with HCC.…”
Section: Signalling Pathwaysmentioning
confidence: 99%
“…Activation of the Notch pathway in vascular endothelial cells is triggered by norepinephrine-induced Jagged 1 expression in breast cancer cells Accumulating evidence indicates that tumor cell-stromal cell interaction may be influenced by the Jagged/Notch pathway (Zeng et al 2005, Sethi et al 2011, Lu et al 2013, Xing et al 2013, Zender et al 2013. Results from recent studies have indicated that the Notch signaling pathway is directly involved in physiological and pathological angiogenesis (Dufraine et al 2008, Benedito et al 2009).…”
Section: Resultsmentioning
confidence: 99%